Increase in Brain Volume After Aneurysmal Subarachnoid Hemorrhage Leads to Unfavorable Outcome: A Retrospective Study Quantified by CT Scan - Qin, Bin; Xiang, Yi; Zheng, Jianfeng; Xu, Rui; Guo, Zongduo; Cheng, Chongjie; Jiang, Li; Wu, Yue; Sun, Xiaochuan; Huang, Zhijian (Frontiers in Neurology, 2021)
Background Primary brain swelling occurs in aneurysmal subarachnoid hemorrhage (aSAH) patients. The absence of a dynamic quantitative method restricts further study of primary brain swelling. This study compared differences in the change rate of brain volume (CRBV) between patients with and without primary brain swelling in the early stage of aSAH. Moreover, the relationship between CRBV and clinical outcomes was evaluated. Methods Patients hospitalized within 24 hours after aSAH were included in this retrospective study. Utilizing a qualitative standard established before the study to recognize primary brain swelling through brain CT after aSAH, clinical outcomes after 3 months of SAH were evaluated with a modified Rankin scale (mRS). The brain volume (BV) of each patient was calculated with a semiautomatic threshold algorithm of 3D-slicer, and the change in brain volume (CIBV) was obtained by subtracting the two extreme values (CIBV=BVmax－BVmin). CRBV was obtained by CIBV/BVmin × 100%. The CRBV values that predicted unfavorable prognoses were estimated. Results In total, 130 subjects were enrolled in the study. The mean CRBV in the non-swelling group and swelling group were 4.37% (±4.77) and 11.87% (±6.84), respectively. Analysis of variance showed significant differences in CIBV, CRBV, blood in the ambient cistern, blood in the lateral ventricle, and lateral ventricular volume among varying modified Fisher scale (mFisher), with higher admission mFisher scale, indicating larger values of these variables. The model showed that for every 1% increase in the CRBV, the probability of poor clinical prognosis increased by a factor of 1.236 (95% CI=1.056~1.446). In the stratified analysis, the odds of worse clinical outcomes increased with increases in the CRBV. Receiver operating characteristic curve analysis showed that the score of CRBV (SCRBV) had diagnostic performance for predicting unfavorable clinical outcomes. Conclusion Primary brain swelling increases brain volume after aSAH. The CRBV quantified by 3D-Slicer can be used as a volumetric representation of the degree of brain swelling. A larger CRBV in the early stage of aSAH is associated with poor prognosis. The CRBV can be used as a neuroimaging biomarker of early brain injury after bleeding and may be an effective predictor of patients' clinical prognoses.